Manipulasi Linguistik sebagai Instrumen Politik dalam Animal Farm: Sebuah Analisis Wacana Kritis - Parlindungan Pardede; Yumna Rasyid; Miftahulkhairah Anwar (Universitas Mulawarman, 2023)
Politics and language are inextricably linked, and the relationship between the two has long been the subject of philosophical and linguistic study. Through critical discourse analysis, the contemporary linguistic practice seeks to examine language as a form of social practice. Thus, political discourse is seen as a discourse oriented towards concealing power for manipulative purposes, legitimizing discourse practices, and imposing ideologies. This study analyzes the use of linguistic manipulation in George Orwell's